Development of the Inactivated QazCovid-in Vaccine: Protective Efficacy of the Vaccine in Syrian Hamsters - Zhugunissov, Kuandyk; Zakarya, Kunsulu; Khairullin, Berik; Orynbayev, Mukhit; Abduraimov, Yergali; Kassenov, Markhabat; Sultankulova, Kulyaisan; Kerimbayev, Aslan; Nurabayev, Sergazy; Myrzakhmetova, Balzhan; Nakhanov, Aziz; Nurpeisova, Ainur; et al. (Frontiers in Microbiology, 2021)
In March 2020, the first cases of the human coronavirus disease COVID-19 were registered in Kazakhstan. We isolated the SARS-CoV-2 virus from clinical materials from some of these patients. Subsequently, a whole virion inactivated candidate vaccine, QazCovid-in, was developed based on this virus. To develop the vaccine, a virus grown in Vero cell culture was used, which was inactivated with formaldehyde, purified, concentrated, sterilized by filtration, and then adsorbed on aluminum hydroxide gel particles. The formula virus and adjuvant in buffer saline solution were used as the vaccine. The safety and protective effectiveness of the developed vaccine were studied in Syrian hamsters. The results of the studies showed the absolute safety of the candidate vaccine in the Syrian hamsters. When studying the protective effectiveness, the developed vaccine with an immunizing dose of 5 μg/dose specific antigen protected animals from a wild homologous virus at a dose of 104.5 TCID50/mL. The candidate vaccine induced the formation of virus-neutralizing antibodies in vaccinated hamsters at titers of 3.3 ± 1.45 log2 to 7.25 ± 0.78 log2, and these antibodies were retained for 6 months (observation period) for the indicated titers. No viral replication was detected in vaccinated hamsters, protected against the development of acute pneumonia, and ensured 100% survival of the animals. Further, no replicative virus was isolated from the lungs of vaccinated animals. However, a virulent virus was isolated from the lungs of unvaccinated animals at relatively high titers, reaching 4.5 ± 0.7 log TCID50/mL. After challenge infection, 100% of unvaccinated hamsters showed clinical symptoms (stress state, passivity, tousled coat, decreased body temperature, and body weight, and the development of acute pneumonia), with 25 ± 5% dying. These findings pave the way for testing the candidate vaccine in clinical human trials.